Faktor-faktor Pendukung yang Mempengaruhi Minat Siswa dalam Pemilihan Jurusan di Perguruan Tinggi di MAN 1 Kota Bukittinggi - Aprilia, Aisyah Bunga; Syawaluddin, Syawaluddin (TSAQOFAH, 2023)
Education is one way for individuals to explore their potential. Education is a necessity of human rights. Every individual has the right to receive education according to his wishes and needs. Interest in continuing education at tertiary institutions is of course the desire of every individual. So in this case it is necessary to study the factors that support students’ interest in continuing higher education. In describing these factors, researchers used a qualitative approach with interview and observation methods. Based on the results of research conducted that the supporting factors of student interest in MAN 1 Bukittinggi City are influenced by internal or external factors and external factors.